Expectations, Outcomes, and Challenges of Modern Code Review - Bird, Christian; Bacchelli, Alberto (Proceedings of the International Conference on Software Engineering, 2013)
Code review is a common software engineering practice employed both in open source and industrial contexts. Review today is less formal and more "lightweight" than the code inspections performed and studied in the 70s and 80s. We empirically explore the motivations, challenges, and outcomes of tool-based code reviews. We observed, interviewed, and surveyed developers and managers and manually classified hundreds of review comments across diverse teams at Microsoft. Our study reveals that while finding defects remains the main motivation for review, reviews are less about defects than expected and instead provide additional benefits such as knowledge transfer, increased team awareness, and creation of alternative solutions to problems. Moreover, we find that code and change understanding is the key aspect of code reviewing and that developers employ a wide range of mechanisms to meet their understanding needs, most of which are not met by current tools. We provide recommendations for practitioners and researchers.